Population pharmacokinetics of ϵ-aminocaproic acid in adolescents undergoing posterior spinal fusion surgery - Stricker, P. A. (Br J Anaesth, 2015)
BACKGROUND: Despite demonstrated efficacy of ϵ-aminocaproic acid (EACA) in reducing blood loss in adolescents undergoing spinal fusion, there are no population-specific pharmacokinetic data to guide dosing. The aim of this study was to determine the pharmacokinetics of EACA in adolescents undergoing spinal fusion surgery and make dosing recommendations. METHODS: Twenty children ages 12–17 years were enrolled, with 10 children in each of two groups based on diagnosis (idiopathic scoliosis or non-idiopathic scoliosis). Previously reported data from infants undergoing craniofacial surgery were included in the model to enable dosing recommendations over a wide range of weights, ages, and diagnoses. A population non-linear mixed effects modelling approach was used to characterize EACA pharmacokinetics. RESULTS: Population pharmacokinetic parameters were estimated using a two-compartment disposition model with allometrically scaled weight and an age effect on clearance. Pharmacokinetic parameters for the typical patient were a plasma clearance of 153 ml min(−1) 70 kg(−1) (6.32 ml min(−1) kg(−0.75)), intercompartmental clearance of 200 ml min(−1) 70 kg(−1) (8.26 ml min(−1) kg(−0.75)), central volume of distribution of 8.78 litre 70 kg(−1) (0.13 litre kg(−1)), and peripheral volume of distribution of 15.8 litre 70 kg(−1) (0.23 litre kg(−1)). Scoliosis aetiology did not have a clinically significant effect on drug pharmacokinetics. CONCLUSIONS: The following dosing schemes are recommended according to patient weight: weight <25 kg, 100 mg kg(−1) loading dose and 40 mg kg(−1) h(−1) infusion; weight ≤25 kg–<50 kg, 100 mg kg(−1) loading dose and 35 mg kg(−1) h(−1) infusion; and weight ≥50 kg, 100 mg kg(−1) loading dose and 30 mg kg(−1) h(−1) infusion. An efficacy trial employing this dosing strategy is warranted. CLINICAL TRIAL REGISTRATION: NCT01408823.